2021
DOI: 10.1002/gch2.202100004
|View full text |Cite
|
Sign up to set email alerts
|

The COVID‐19 Menace

Abstract: Coronavirus disease 2019 (COVID‐19) is caused by the new severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2), which binds to ectoenzyme angiotensin‐converting enzyme 2. It is very contagious and is spreading rapidly around the world. Until now, coronaviruses have mainly been associated with the aerodigestive tract due to the presence of a monobasic cleavage site for the resident transmembrane serine protease 2. Notably, SARS‐CoV‐2 is equipped with a second, polybasic cleavage site for the ubiquitous f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 162 publications
(134 reference statements)
0
4
0
Order By: Relevance
“…Previous reports have suggested that patients with cancer are more susceptible to infections, and several bioinformatics analyses have shown that cancer tissues have higher TMPRSS2 expression levels than matched healthy tissues in lung and stomach cancer ( 24 , 25 ). As previously reported, patients with COVID-19 usually exhibit multi-organ damage, especially aerodigestive disease ( 26 ). We can speculate that a high expression of TMPRSS2 in these tissues facilitates the susceptibility to SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 63%
“…Previous reports have suggested that patients with cancer are more susceptible to infections, and several bioinformatics analyses have shown that cancer tissues have higher TMPRSS2 expression levels than matched healthy tissues in lung and stomach cancer ( 24 , 25 ). As previously reported, patients with COVID-19 usually exhibit multi-organ damage, especially aerodigestive disease ( 26 ). We can speculate that a high expression of TMPRSS2 in these tissues facilitates the susceptibility to SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 63%
“…Arriving in huge quantities, they were true stars, and they had a huge impact on taming the COVID-19 pandemic in many geographical regions. 107…”
Section: Biological Roles Of Mrna-based Medicines Vaccinesmentioning
confidence: 99%
“…specific symptoms of COviD-19, such as fever, cough, fatigue, loss of smell and taste or symptoms of respiratory distress syndrome are usually found in adults [1] and much less frequently in young adults [2]. nevertheless, its high infectiousness and potential to be life-threatening make it a significant issue for individuals of all ages [3]. recent studies on the COviD-19 pandemic suggest that experiences of uncertainty, fear of infection and disease, self-isolation, quarantine or lack of physical activity are highly stress-inducing factors [4], triggering psychological reactions in people similar to those observed in other extreme situations [5].…”
Section: Introductionmentioning
confidence: 99%